Intrathecal baclofen as emergency treatment alleviates severe intractable autonomic dysreflexia in cervical spinal cord injury. (4th July 2021) - Delhaas, Elmar M.; Frankema, Sander P.G.; Huygen, Frank J.P.M.
Abstract : Context: Episodic attacks of autonomic dysreflexia (AD) are regularly experienced by patients with a spinal cord injury (SCI) on T6 or higher levels. The episodes can result in a pounding headache, flushing, blurred vision, anxiety, a stroke, posturing, hyperthermia, retinal bleeding, seizures, myocardial ischemia, cardiac arrhythmias, and death. The observed associated bradycardia is explained as a baroreceptor reflex response to the high blood pressure. Intrathecal baclofen (ITB) has been used to treat chronic AD. This case highlights the occurrence of intractable AD after removal of the ITB delivery system because of a pump pocket infection. We describe the benefit of ITB as an emergency treatment for intractable AD. Findings: A 53-year-old male suffered from spasticity and AD after a C5 ASI B SCI in 2002 was successfully treated with ITB for 14 years. He developed Staphylococcus aureus and Pseudomonas aeruginosa cellulitis at the orifice of his suprapubic catheter, which caused an abscess in the pump pocket. To prevent a withdrawal syndrome, the medication was reduced in three steps of 25%, and the pump was explanted. Postoperatively, he experienced severe AD and was treated with clonazepam, clonidine, and urapidil. The next day, the severely fluctuating blood pressure and pulse rate were no longer controllable with the medication. At L2-3, a temporary external intrathecal catheter for reinitiating ITB was inserted. With this treatment, the AD and the spasticity symptoms could be controlled. Conclusion/Clinical Relevance: The case demonstrated that refractory AD could be managed with ITB in an emergency.